Restaurant online reservation system - Amenuddin, Alias (2014)
Restaurant Online Reservation System is developed for customer, staff and manager of Horizon Garden Restaurant. This system helps customer with the reservation and staff with the reservation management. In the existing system, the process is conducted manually that are wasting time and energy. Therefore, propose system is to change the current process to computerized system. The methodology that has been applied during project development is the prototype model. The advantages of the prototype model are it can be an early act or representation of the final product and this method can reduce risk and limits expenses and costs. In the development of the propose system Microsoft Visual Studio 2010 has been used as the programming tool with the SQL Server 2010 as the database.